1,000 product designs : form, function, and technology from around the world - Chan, Eric (Rockport Publishers, 2010)
With so much competition on the shelf, products must uniquely distinguish themselves and become must have items for consumers. This inspirational volume features 1000 of the best product designs in recent years, judged by award winning Ecco Design